Serotonergic Modulation of Intrinsic Functional Connectivity - Schaefer, Alexander; Burmann, Inga; Regenthal, Ralf; Arélin, Katrin; Barth, Claudia; Pampel, André; Villringer, Arno; Margulies, Daniel S.; Sacher, Julia (Current biology, 2014)
Serotonin functions as an essential neuromodulator that serves a multitude of roles, most prominently balancing mood [1]. Serotonergic challenge has been observed to reduce intrinsic functional connectivity in brain regions implicated in mood regulation [2–4]. However, the full scope of serotonergic action on functional connectivity in the human brain has not been explored. Here, we show evidence that a single dose of a serotonin reuptake inhibitor dramatically alters functional connectivity throughout the whole brain in healthy subjects (n = 22). Our network-centrality analysis reveals a widespread decrease in connectivity in most cortical and subcortical areas. In the cerebellum and thalamus, however, we find localized increases. These rapid and brain-encompassing connectivity changes linked to acute serotonin transporter blockade suggest a key role for the serotonin transporter in the modulation of the functional macroscale connectome. •Single dose of SSRI changes functional architecture of the human brain•This change in intrinsic connectivity occurs within a few hours of SSRI intake•SSRI intake reduces majority of intrinsic connectivity throughout the brain•In contrast, intrinsic connectivity increases in cerebellum and thalamus Schaefer et al. observe global changes in functional connectivity in the brain three hours after a single dose of the SSRI escitalopram. Specifically, a widespread decrease in connectivity in most cortical and subcortical areas was seen as well as synchronized increases in connectivity in thalamus and cerebellum.